2021
DOI: 10.1186/s12884-021-04083-y
|View full text |Cite
|
Sign up to set email alerts
|

The RPOC long axis is a simple indicator for predicting the need of invasive strategies for secondary postpartum hemorrhage in either post-abortion or post-partum women: a retrospective case control study

Abstract: Background The retained products of conception (RPOC) and related conditions (RPOC-ARC) are the main cause of secondary postpartum hemorrhage (sPPH), but there is no clear consensus for their management. The purpose of this study was to characterize those RPOC-ARC that require invasive treatment and those that could be managed more conservatively. Methods We retrospectively analyzed 96 cases of RPOC-ARC that occurred after miscarriage, abortion, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…Matsumura et al reported that ultrasonographic assessment of RPOC focusing on vascularity in combination with size was essential for detecting the high risk of severe postpartum hemorrhage (SPPH) in women with RPOC 27 . Kobayashi et al also suggested that the long axis of RPOC is a simple indicator for predicting women with SPPH who would require invasive procedures 28 . However, in our analysis, consistent significant differences in these factors were not observed between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumura et al reported that ultrasonographic assessment of RPOC focusing on vascularity in combination with size was essential for detecting the high risk of severe postpartum hemorrhage (SPPH) in women with RPOC 27 . Kobayashi et al also suggested that the long axis of RPOC is a simple indicator for predicting women with SPPH who would require invasive procedures 28 . However, in our analysis, consistent significant differences in these factors were not observed between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the RPOC diameters [?] 4 -4.4 cm 6,8) or blood flow in RPOC 7,21) had been associated with heavy bleeding during conservative management of RPOC. However, these studies differ from the present study in several respects.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies differ from the present study in several respects. First, these studies included cases before 20 weeks' gestation [6][7][8]21) . Although the size of RPOC is smaller, trophoblast cell viability is higher in early and mid-pregnancy than in late pregnancy 20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations